Analysing human and system related barriers of TQM in automobile industries using fuzzy DEMATEL approach. (28th February 2022) - Yadav, Ram Nath; Kumar, Devendra; Sharma, Ajay Kumar; Virmani, Naveen
Total quality management methodology has proved by many researchers to give magnificent results to both manufacturing and service industries. In today's globalised era, each and every industry is making meticulous efforts to survive in the marketplace. Industries are well aware of the fact that providing quality products to customers and achieving maximum customer satisfaction are the only key to success. In this paper, 17 potential barriers are identified by extensive literature review and the same has been validated by experts. The barriers are lack of top management commitment, lack of funds, lack of advance manufacturing facilities, employees resistance to change, etc. fuzzy decision making trial and evaluation laboratory (DEMATEL) approach has been applied to analyse potential barriers so as to categorise them into cause and effect categories.